A preliminary study on the antimicrobial properties of damong maria against staphyloccus aureus and streptococcus pyogenes - De Leon, Melanie; Sta. Maria, Sonia; Serraon, Antolin (Adviser).
This research aims to determine the effectivity of the leaves of Artemisia Vulgaris otherwise known as "damong maria" as an agent against Staphylococcus Aureus and Streptoccus pyogenes using the disc diffusion method. The experiment was conducted in vitro using different concentrations of the aqeous extract against the test microorganisms. Based on the measured the test microorganisms. Based on the measured zonez of inhibition, our study shows that 20%, 40%, 60% 80% and 100% concentrations of damong maria aqeous extract are not effective agents against Staphylococcus aureus and Streptococcus pyogenes.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Herbal medicine; Antibiotics